1965
DOI: 10.1103/physrev.140.a304
|View full text |Cite
|
Sign up to set email alerts
|

Electrical Properties of Stannic Oxide Single Crystals

Abstract: The Hall coefficient and electrical resistivity have been measured on single-crystal specimens of «-type Sn02 between 80 and 900°K. Data were obtained on samples in the "as grown" state, as well as on crystals which were thermally equilibrated in oxygen. A single-donor-level analysis on heat-treated crystals with donor concentrations (ND) between 1X10 16 and 5X10 17 cm" 3 resulted in values of the "density-of-states" effective mass m (JNr) =0.22m. Values of the donor ionization energy ED were found to decrease… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0

Year Published

1970
1970
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 114 publications
(32 citation statements)
references
References 18 publications
1
31
0
Order By: Relevance
“…4), and that oxygen vacancies are found in significant concentrations, rising above 10 19 cm −3 for T > 1000 K (using the PBE0 and B97-2 functionals). With the PBE0 and B97-2 functionals, in this range of E F the dominant charge state for the V O is neutral, but at T > 1000 K we find that approximately 2% of the vacancies are thermally ionized, resulting in electron concentrations ranging up to 10 18 cm −3 at T = 1500 K. With the BB1k functional, as the transition level is shallower, a greater proportion of the vacancies are thermally ionized (at T = 1200 K, 27% are in the + and 65% are in the 2+ state), and we find that n 0 and [V O ] are close in value and increase to just above 10 18 cm −3 at T = 1500 K. From these results, 054604-9 we see that, despite such a deep transition level, in reducing conditions significant intrinsic charge carrier concentrations can arise at temperatures above 800 K, in good agreement with experiment [72][73][74]. For T < 800 K, the concentrations we calculate are somewhat lower than experiment; the source of this discrepancy may be residual n-type activity from impurities or other defects which could dominate at reduced temperatures.…”
Section: Charge Carrier and Defect Concentrationssupporting
confidence: 86%
See 2 more Smart Citations
“…4), and that oxygen vacancies are found in significant concentrations, rising above 10 19 cm −3 for T > 1000 K (using the PBE0 and B97-2 functionals). With the PBE0 and B97-2 functionals, in this range of E F the dominant charge state for the V O is neutral, but at T > 1000 K we find that approximately 2% of the vacancies are thermally ionized, resulting in electron concentrations ranging up to 10 18 cm −3 at T = 1500 K. With the BB1k functional, as the transition level is shallower, a greater proportion of the vacancies are thermally ionized (at T = 1200 K, 27% are in the + and 65% are in the 2+ state), and we find that n 0 and [V O ] are close in value and increase to just above 10 18 cm −3 at T = 1500 K. From these results, 054604-9 we see that, despite such a deep transition level, in reducing conditions significant intrinsic charge carrier concentrations can arise at temperatures above 800 K, in good agreement with experiment [72][73][74]. For T < 800 K, the concentrations we calculate are somewhat lower than experiment; the source of this discrepancy may be residual n-type activity from impurities or other defects which could dominate at reduced temperatures.…”
Section: Charge Carrier and Defect Concentrationssupporting
confidence: 86%
“…If, instead, this level can be attributed to V O , which becomes more dominant once the hydrogen donors are removed, then our calculated value is also in good agreement with this result. We note that a level at 0.28-0.35 eV has been observed in many n-type samples [75,[164][165][166] (as has the ∼0.15 eV level) [73][74][75]167], and that, in a study on SnO 2 nanoparticles [168], a switching of activation energy from 0.11 to 0.35 eV was observed in the largest nanoparticle when changing from low to high temperature.…”
Section: Sn Omentioning
confidence: 51%
See 1 more Smart Citation
“…͑4͒. The mobilities are typically an order of magnitude lower than the values measured in single-crystalline samples of similar carrier density, 10,11 which already points to the importance of the grain boundaries in limiting the carrier transport. First, we will describe the results for the respective samples, mainly in terms of the energy band diagrams.…”
Section: Methodsmentioning
confidence: 88%
“…Figure 4 shows that the electron concentration in the SnO 2 film is in the order of 10 19 cm Ϫ3 , which agrees with the value of bulk single crystal SnO 2 . 24 Studies of undoped single crystal bulk SnO 2 showed that the Hall mobility of electrons at room temperature, for an electron concentration of about 10 19 cm Ϫ3 , is around 90 cm 2 /V s. 24 In the present work, the mobility at room temperature is about 37 cm 2 /V s. Planar defects, such as CSPs and antiphase boundaries as well as interfaces, have been shown to act as scattering centers in nonstoichiometric rutile TiO 2 , 25 which significantly reduces the conductivity with respect to perfect crystal. The main defects observed in the SnO 2 thin film fabricated by fPLD are antiphase boundaries ͑coherent CSPs͒ and misfit dislocation at the interface.…”
Section: Discussionmentioning
confidence: 97%